2015
DOI: 10.3390/e17063913
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Based Privacy against Profiling of User Mobility

Abstract: Location-based services (LBSs) flood mobile phones nowadays, but their use poses an evident privacy risk. The locations accompanying the LBS queries can be exploited by the LBS provider to build the user profile of visited locations, which might disclose sensitive data, such as work or home locations. The classic concept of entropy is widely used to evaluate privacy in these scenarios, where the information is represented as a sequence of independent samples of categorized data. However, since the LBS queries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Xiao et al [11] [19] studied how to protect location privacy under temporal correlations with an optimal differentially private mechanism. Rodriguez-Carrion et al [25] also studied the effect of temporal dependencies on entropybased location privacy metric. They proposed a new privacy metric entropy rate and perturbative mechanisms based on it, which can be an alternative LPPM in our framework for protecting spatiotemporal event privacy.…”
Section: Runtimementioning
confidence: 99%
“…Xiao et al [11] [19] studied how to protect location privacy under temporal correlations with an optimal differentially private mechanism. Rodriguez-Carrion et al [25] also studied the effect of temporal dependencies on entropybased location privacy metric. They proposed a new privacy metric entropy rate and perturbative mechanisms based on it, which can be an alternative LPPM in our framework for protecting spatiotemporal event privacy.…”
Section: Runtimementioning
confidence: 99%
“…However, tracking user mobility rises privacy concerns. In [16] we analyzed privacy-enhancing mechanisms based on information theory concepts, such as entropy, applied to locations and mobility profiling scenarios. We have shown that the theory applicable to these low alphabet cardinality and memoryless processes, cannot be directly applied to more complex cases such as the mobility profiles of users.…”
Section: B Analyzing the Impact Of Individual Movementsmentioning
confidence: 99%
“…Xiao et al [9] [18] studied how to protect location privacy under temporal correlations with an optimal differentially private mechanism. Rodriguez-Carrion et al [23] also studied the effect of temporal dependencies on entropy-based location privacy metric. They proposed a new privacy metric entropy rate and perturbative mechanisms based on it, which can be an alternative LPPM in our framework for protecting spatiotemporal event privacy.…”
Section: Runtimementioning
confidence: 99%